Research status and prospect of laser additive manufacturing technology for high performance gradient functional materials - CUI Xue; ZHANG Song; ZHANG Chun-hua; WU Chen-liang; WANG Qiang; DONG Shi-yun (Cailiao gongcheng, 2020)
Among the manufacturing methods of high performance gradient functional materials, laser additive manufacturing technology can achieve the materials with gradient microstructure and property through precisely controlling the powder feeding and corresponding process adjustment, providing a new way to prepare high performance gradient functional materials more conveniently and efficiently. The basic principles and classification of laser additive manufacturing technology for high performance gradient functional materials were introduced in this paper, and the research progress in manufacturing high performance gradient functional materials by laser additive manufacturing technology at home and abroad was summarized. Furthermore, the shortcomings of this research field in material selection, process optimization and process monitoring were proposed, and its future research directions, such as the establishment of standard systems, in-depth theoretical research and the development of new manufacturing systems, were prospected, which provide guidance for the research of laser additive manufacturing technology for high performance gradient functional materials.